(untitled) (Open Academia: Journal of Scholarly Research, 2023)
According to experts, in the next 20 years, due to a sharp decrease in water resources, the water shortage in our country will increase fivefold. According to the shortage of water from Uzbeks, it is included in the ranks of red regions. Fruit production will be limited in the coming years due to water scarcity